PEMANFAATAN MEDIA QUIZIZZ PADA LATIHAN SOAL UNTUK MENDORONG KEAKTIFAN BELAJAR SISWA DALAM PEMBELAJARAN DARING [THE UTILIZATION OF QUIZIZZ MEDIA IN PROBLEMS TO IMPROVE STUDENTS’ LEARNING ACTIVENESS IN ONLINE LEARNING] - Loupatty, Fredrik David; Saragih, Melda Jaya (JOHME: Journal of Holistic Mathematics Education, 2021)
This paper investigates student learning activeness as an important part of the formation and development of student potential. The aim of this paper is to describe the use of quizzes in lesson plans (practice questions) to encourage student activeness in online learning. Doing a field practicum program online presents its own challenges for teachers. One of them is related to the responses of students who are less active in learning. The solution applied is to use technology media for learning, namely using Quizizz to do practice exercises online. Divided into 10 implementation steps, the initial 8 steps are general steps such as making an online quiz on Quizizz while the last 2 steps are an adaptation done by the teacher himself. The implementation of this media in doing exercises shows that students are encouraged to be actively involved in learning. It can be seen in the attitude of those who are actively discussing (question & answer). This emphasizes the real practice of a Christian teacher in living his salvation through holistic learning design, for example by utilizing technology in the classroom to encourage active student involvement. This research has many weaknesses such as data validity, problem deepening, and technical problems in using Quizziz. This can be an evaluation and input for writers and readers.BAHASA INDONESIA ABSTRACT: Paper ini dibuat untuk melihat hubungan keaktifan belajar siswa dalam pembelajaran sebagai bagian penting dalam pembentukan dan pengembangan potensi siswa. Tujuan paper ini adalah untuk memaparkan pemanfaatan Quizizz dalam pembelajaran untuk mendorong keaktifan siswa dalam pembelajaran online. PPL yang dilaksanakan secara online memberikan tantangan tersendiri bagi pengajar, di antaranya: berkaitan dengan respons siswa yang kurang aktif dalam pembelajaran. Solusi yang diterapkan adalah memanfaatkan media teknologi untuk pembelajaran yaitu menggunakan Quizizz untuk melakukan latihan soal secara online. Dibagi menjadi 10 langkah penerapan, 8 langkah awal merupakan langkah umum seperti membuat kuis online pada Quizizz sedangkan 2 langkah terakhir merupakan adaptasi yang dilakukan oleh pengajar sendiri. Pengimplementasian media ini dalam melakukan latihan soal menunjukan adanya dorongan untuk siswa dapat terlibat aktif di dalam pembelajaran. Terlihat dari sikap mereka yang aktif berdiskusi (tanya & jawab). Hal ini menekankan praktik nyata seorang pengajar Kristen dalam menghidupi keselamatannya melalui perancangan pembelajaran yang holistik misalnya dengan memanfaatkan teknologi di kelas untuk mendorong keterlibatan aktif siswa. Penelitian ini memiliki banyak kelemahan seperti kevalidan data, pendalaman masalah, serta gangguan teknis dalam penggunaan Quizizz. Hal ini dapat menjadi evaluasi dan masukan bagi penulis maupun pembaca.